Effect on mechanical properties of aluminium alloy composites on adding ash as reinforcement material - Khan, Mohd Zafaruddin; Anas, Mohd; Husain, Ather; Haque, Md Irshadul; Rasheed, Kamran (Journal of Metals, Materials and Minerals, 2015)
To produce Al-matrix cast particle composites, wettability of the ceramic particles by liquid Al is essential. To improve wettability of the solution, few elements such as Mg and Si are added into Al melt to incorporate the ceramic particles. The present investigation has been focussed on the utilization of abundant available industrial waste such as fly ash and bagasse ash in useful manner by dispersing it into Eutectic Al-Si alloy LM6 Containing 10.58% Si to produce composites by liquid casting route. The mechanical properties such as Brinell Hardness and Ultimate tensile strength has been investigated. The test results of the mechanical properties have indicated that the ultimate tensile strength varies from 112.6 kN/mm2 to 180 kN/mm2 with maximum value at 10wt % fly ash +10wt % bagasse ash and hardness varies from 52 BHN to 80 BHN with maximum value at 10wt% fly ash + 10wt% bagasse ash as reinforcement in the matrix metal. It was concluded that 10wt% fly ash +10wt% bagasse ash can be used as reinforcement in aluminium composites and the produced composites could be used in automobile industry for the production of lighter & strong engine blocks, pistons and other components.